2017
DOI: 10.7860/jcdr/2017/26958.9953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluoxetine on the Hippocampus of Wistar Albino Rats in Cold Restraint Stress Model

Abstract: Introduction: Stress has been known to be a potential modulator of learning and memory. Long term stress can lead to depression. Fluoxetine is a selective serotonin reuptake inhibitor group of drug used in the treatment of depression. Aim:The present study was conducted to evaluate the potential of Fluoxetine on cold restraint induced stress in the hippocampus of Wistar rats. Materials and Methods:A total of 18 male wistar albino rats were divided randomly into three groups (n=6). Group 1 was the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…As expected, the effect of oleuropein, on GSH and TBARS, was superior to that of fluoxetine. Fluoxetine ameliorated Cort-induced lipid peroxidation and GSH depletion, and this was in accordance with Jayakumar et al, and Rebai et al 54,55 . The antioxidant activity of oleuropein was previously reported in various tissues 56,57 and in the brain 58,59 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As expected, the effect of oleuropein, on GSH and TBARS, was superior to that of fluoxetine. Fluoxetine ameliorated Cort-induced lipid peroxidation and GSH depletion, and this was in accordance with Jayakumar et al, and Rebai et al 54,55 . The antioxidant activity of oleuropein was previously reported in various tissues 56,57 and in the brain 58,59 .…”
Section: Discussionsupporting
confidence: 89%
“…The three main brain monoamines (noradrenaline, 5-HT and dopamine) regulate several behavioral functions and play critical role in learning, sleep, mood, anxiety, motor coordination, and learning 54 . An association between their deficiency and the pathogenesis of depression and its symptoms has been suggested 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Results of our study showed that the level of serum CORT was significantly increased in acute CRS group as compared to either control or omega‐3 group which is compatible with Jayakumar, Raghunath, Ilango, Vijayakumar, and Vijayaraghavan () who reported that exposure of animals to CRS led to upregulation of stress hormones by hyper activation of HPA axis which can also alter antioxidant system.…”
Section: Discussionsupporting
confidence: 89%
“…The increased 5-HT and dopamine levels could be the result of the deleterious activities of noise on the hippocampus (Jayakumar, 2017).…”
Section: Resultsmentioning
confidence: 99%